Lamb performance under different hibernation feeding systems (Research, Society and Development, 2023)
Sheep farming systems, mainly in the state of Rio Grande do Sul, are managed under natural pastures with low investment, which at certain stages of the year do not meet maintenance requirements. Therefore, during the winter period, the introduction of forage species and the use of food supplementation become efficient strategies to improve lamb performance in this sense, the objective of the present study was to evaluate the performance of 24 Texel lambs, with an average body weight of 25.79 ± 3.21 kg and an initial average age of six months, under different feeding systems on ryegrass pasture. The experiment was conducted in an area belonging to the Federal University of Santa Maria/RS, Brazil. The grazing method adopted was continuous stocking with a variable stocking rate. The food systems consisted of ryegrass (Lolium multiflorum Lam.) with 150 kg of nitrogen (N) ha-1, ryegrass intercropped with legumes with 75 kg of N ha-1 and ryegrass with a supplement supply in the proportion of 1% of the weight body weight (BW) with 75 kg of N ha-1. The experimental design was completely randomized, with repeated measurements over time, with three treatments and four area replications. The final body weight and average daily gain of lambs in the food system with supplement inclusion were, respectively, 15.28% and 30.76% higher when compared to lambs in the food system with inclusion of legumes and, respectively, 6.50% % and 11.47% higher compared to the ryegrass-only food system. It is concluded that lambs fed with ryegrass and receiving supplements have greater body performance compared to those fed exclusively on pasture.